Zlepšení výkonosti podniku - Čechová, Aneta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Bakalářská práce se zabývá hodnocením výkonnosti podniku RYOR, s.r.o. využitím metod finanční analýzy. Následně budou zpracovány návrhy na zlepšení výkonnosti podniku. Práce má dvě hlavní části – teoretickou a analytickou

This bachelor thesis focuses on an evaluation of financial situation of RYOR, a.s. through the use of financial analysis methods. After, there will be made proposals on business performance improvement. The thesis is divided into two parts – theoretical and analytical.
Business Performance Improvement
Keywords: finanční analýza; absolutní ukazatele; rentabilita; likvidita; zadluženost; financial analysis; absolute indicators; profitability; liquidity; indebtedness